2005
DOI: 10.1074/jbc.m414142200
|View full text |Cite
|
Sign up to set email alerts
|

Antisense-mediated Inhibition of the Plasma Membrane Calcium-ATPase Suppresses Proliferation of MCF-7 Cells

Abstract: Alterations in Ca2؉ signaling may contribute to tumorigenesis and the mechanism of action of some anticancer drugs. The plasma membrane calcium-ATPase (PMCA) is a crucial controller of intracellular Ca 2؉ signaling. Altered PMCA expression occurs in the mammary gland during lactation and in breast cancer cell lines. Despite this, the consequences of PMCA inhibition in breast cancer cell lines have not been investigated. In this work, we used Tet-off PMCA antisense-expressing MCF-7 cells to assess the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 43 publications
1
23
1
3
Order By: Relevance
“…On the other hand, while the expression of PMCA4b was relatively low in control cells, it was highly upregulated upon treatments. In contrast to previous findings [53], we could not detect PMCA2 (neither PMCA3) protein expression either in control or treated MCF-7 cells using isoform specific antibodies (NR2 and NR3).…”
Section: Combined Treatment By Valerate and Pma Further Increased Pmccontrasting
confidence: 99%
“…On the other hand, while the expression of PMCA4b was relatively low in control cells, it was highly upregulated upon treatments. In contrast to previous findings [53], we could not detect PMCA2 (neither PMCA3) protein expression either in control or treated MCF-7 cells using isoform specific antibodies (NR2 and NR3).…”
Section: Combined Treatment By Valerate and Pma Further Increased Pmccontrasting
confidence: 99%
“…Rather, a cross-talk exists between Ca 2+ signaling and various cellular signaling systems that control cell survival, proliferation, differentiation and apoptosis. An additional argument in support of this idea is the involvement of various PMCA isoforms both in cell proliferation [64,96,97] and apoptosis [9,76,98,99]. Suppressed proliferation of breast cancer MCF-7 cells or induced apoptosis in vascular smooth muscle cells via antisense-mediated PMCA inhibition were published earlier [97,99].…”
Section: Discussionmentioning
confidence: 95%
“…Monteith and his group (12) observed that the expression of different isoforms of the PMCA is changed in breast cancer cells and that PMCA2 expression is significantly increased (32). Furthermore, inhibition of PMCA using siRNA decreased proliferation of MCF-7 human breast cancer cells (33). In recent years, there has been accumulating evidence that the TRPV6 epithelial calcium entry channel is involved in breast cancer progression.…”
Section: Discussionmentioning
confidence: 99%